Analysis of Fluid Balance as Predictor of Length of Assisted Mechanical Ventilation in Children Admitted to Pediatric Intensive Care Unit (PICU) - Praveen Unki; Sushma Save (International Journal of Pediatrics)
Background. Ventilator-associated lung injury (VALI) is a devastating complication of assisted mechanical ventilation (AMV) and is one of the root causes of prolonged AMV. Many strategies were made to decrease the effect of the same. This study is conducted to determine the association of prolonged AMV with fluid balance and pediatric index of mortality 2 (PIM2) score. Methods. This prospective observational study was carried out in a PICU of a tertiary care centre over a period of 12 months. Patient’s fluid balance was calculated by tabulating fluid input-output over initial 48 hours of AMV. The PIM2 score on admission was documented. The association between qualitative variables was assessed by a chi-square test. Comparison of quantitative data measured between cases with duration of AMV≥7 days and <7 days was done using the Mann–Whitney U test. Correlation between quantitative data was done by using the Pearson product moment correlation. Results. Out of 40 patients, 27 patients who had ≥15% positive fluid balance required prolonged mechanical ventilation. Similarly, 27 patients with PIM2 score≥5 required prolonged AMV. On applying the Pearson chi-square test, we found a significant association between positive fluid balance and prolonged mechanical ventilation (P value=2.25×10−7 (<0.05)). Likewise, a statistically significant association was found between PIM2 score and prolonged ventilation (P value=1.19×10−5 (<0.05)). Conclusion. There is a significant association of prolonged AMV with positive fluid balance (>15%) and PIM2 score (>5). By strict maintenance of fluid balance with appropriate intervention, the length of AMV and PICU stay can be decreased.